Iron or sulfur respiration—an adaptive choice determining the fitness of a natronophilic bacterium Dethiobacter alkaliphilus in geochemically contrasting environments - Zavarzina, Daria G.; Merkel, Alexander Yu; Klyukina, Alexandra A.; Elizarov, Ivan M.; Pikhtereva, Valeria A.; Rusakov, Vyacheslav S.; Chistyakova, Nataliya I.; Ziganshin, Rustam H.; Maslov, Alexey A.; Gavrilov, Sergey N. (Frontiers in Microbiology, 2023)
Haloalkaliphilic microorganisms are double extremophiles functioning optimally at high salinity and pH. Their typical habitats are soda lakes, geologically ancient yet widespread ecosystems supposed to harbor relict microbial communities. We compared metabolic features and their determinants in two strains of the natronophilic species Dethiobacter alkaliphilus, the only cultured representative of the class “Dethiobacteria” (Bacillota). The strains of D. alkaliphilus were previously isolated from geographically remote Mongolian and Kenyan soda lakes. The type strain AHT1T was described as a facultative chemolithoautotrophic sulfidogen reducing or disproportionating sulfur or thiosulfate, while strain Z-1002 was isolated as a chemolithoautotrophic iron reducer. Here, we uncovered the iron reducing ability of strain AHT1T and the ability of strain Z-1002 for thiosulfate reduction and anaerobic Fe(II) oxidation. Key catabolic processes sustaining the growth of both D. alkaliphilus strains appeared to fit the geochemical settings of two contrasting natural alkaline environments, sulfur-enriched soda lakes and iron-enriched serpentinites. This hypothesis was supported by a meta-analysis of Dethiobacterial genomes and by the enrichment of a novel phylotype from a subsurface alkaline aquifer under Fe(III)-reducing conditions. Genome analysis revealed multiheme c-type cytochromes to be the most probable determinants of iron and sulfur redox transformations in D. alkaliphilus. Phylogeny reconstruction showed that all the respiratory processes in this organism are likely provided by evolutionarily related early forms of unconventional octaheme tetrathionate and sulfite reductases and their structural analogues, OmhA/OcwA Fe(III)-reductases. Several phylogenetically related determinants of anaerobic Fe(II) oxidation were identified in the Z-1002 genome, and the oxidation process was experimentally demonstrated. Proteomic profiling revealed two distinct sets of multiheme cytochromes upregulated in iron(III)- or thiosulfate-respiring cells and the cytochromes peculiar for Fe(II) oxidizing cells. We suggest that maintaining high variation in multiheme cytochromes is an effective adaptive strategy to occupy geochemically contrasting alkaline environments. We propose that sulfur-enriched soda lakes could be secondary habitats for D. alkaliphilus compared to Fe-rich serpentinites, and that the ongoing evolution of Dethiobacterales could retrace the evolutionary path that may have occurred in prokaryotes at a turning point in the biosphere’s history, when the intensification of the sulfur cycle outweighed the global significance of the iron cycle.